Decoding metastatic microenvironments through single-cell omics reveals new insights into niche dynamics and tumor evolution. - Fengshuo Liu; Xiang H-F Zhang (PLoS Biology)
Metastasis is the predominant cause of cancer mortality, primarily driven by complex tumor-host interactions within specialized metastatic niches. Recent advances in single-cell technologies have provided unprecedented insights into metastatic niche formation, evolution and function, including how primary tumors precondition distant organs for metastases and how disseminated tumor cells dynamically interact with host cells to modulate their environments. Integrated single-cell studies across multiple cancer types have also revealed divergent and convergent metastatic adaptation strategies. These findings collectively highlight metastasis as a dynamic, cooperative process shaped by intricate tumor-host interactions, and provide a foundation for novel therapeutic strategies targeting components of the metastatic microenvironment.